Fotodegradasi Rhodamin B Menggunakan Komposit Perak Fosfat- Hidroksiapatit dari Tulang Ikan Cakalang (Katsuwonus pelamis) - Lusiana Eka Sari; Audy D. Wuntu; Max R.J. Runtuwene; Lidya Irma Momuat (Jurnal Ilmiah Sains, 2023)
Hydroxyapatite (HAp) treated with silver would produce silver phosphate (Ag3PO4), which is a semiconducting material and can degrade synthetic dyes. This study aimed to synthesize a composite material with the main components of HAp from skipjack (Katsuwonus pelamis) bone and Ag3PO4 used to degrade the synthetic dye Rhodamin B (RB) in aqueous solution. The resulting material was characterized using X-Ray Diffraction (XRD), Scanning Electron Microscopy with Energy-Dispersive X-Ray (SEM-EDX), and Fourier Transform Infrared (FTIR) Spectroscopy. The photodegradation of Rhodamine B was evaluated under visible light irradiation with variations in the number of composites, irradiation intensity, and irradiation time. Characterization results showed the formation of Ag3PO4/HAp composites, and photodegradation tests showed that the higher the amount of photocatalyst used and the higher the light intensity, the more synthetic dyes were degraded. Keywords: Ag3PO4; photodegradation; hydroxyapatite; rhodamine B; skipjack tuna bone